2020
DOI: 10.1002/hfm.20830
|View full text |Cite
|
Sign up to set email alerts
|

Continuous evaluation of participants’ perceptions of impact: Applying a boundary object in organizational‐level interventions

Abstract: Workplaces across Europe experience increasing problems with work-related strain and stress. Consequently, they are confronted with the need for stress-preventive interventions that target the sources of stress. A matter of current debate is how to continuously evaluate an organizational-level intervention and gain insight into progress and participants' perceptions of its impact; however, empirical data are lacking. Therefore, we conducted a qualitative study in three workplaces-two in information technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Visibility tools are an effective method to externalize tacit individual knowledge about the intervention to explicit individual knowledge (through individual ratings of progress) and from explicit knowledge to explicit collective knowledge (through dialogue about individuals' rating). Ipsen et al (2020) found that the visibility tool was indeed successful in increasing awareness and visibility of the intervention progress, and it was perceived as a signal to workers that management valued workers' opinions. The challenges of the tool related to the definition of progress, for example it was not clear how much progress warranted one building block being added to the wall and workers found it hard to imagine the end goal, i.e., how much did a building block count towards achieving the final goal.…”
Section: Evaluations Of Organizational Interventions Commonly Occur A...mentioning
confidence: 98%
See 1 more Smart Citation
“…Visibility tools are an effective method to externalize tacit individual knowledge about the intervention to explicit individual knowledge (through individual ratings of progress) and from explicit knowledge to explicit collective knowledge (through dialogue about individuals' rating). Ipsen et al (2020) found that the visibility tool was indeed successful in increasing awareness and visibility of the intervention progress, and it was perceived as a signal to workers that management valued workers' opinions. The challenges of the tool related to the definition of progress, for example it was not clear how much progress warranted one building block being added to the wall and workers found it hard to imagine the end goal, i.e., how much did a building block count towards achieving the final goal.…”
Section: Evaluations Of Organizational Interventions Commonly Occur A...mentioning
confidence: 98%
“…How organizational members make sense of the intervention may be as important to the sustainability of the intervention, compared to the scientific evaluation . In one study, Ipsen et al (2020) explored the impact of using a visible evaluation tool (e.g., using building blocks building a wall to indicate the level of progress) to encourage dialogue about the progress of the intervention and the extent to which action plans were being implemented. Visibility tools are an effective method to externalize tacit individual knowledge about the intervention to explicit individual knowledge (through individual ratings of progress) and from explicit knowledge to explicit collective knowledge (through dialogue about individuals' rating).…”
Section: Evaluations Of Organizational Interventions Commonly Occur A...mentioning
confidence: 99%
“…We propose to utilize this approach to improve the employees' (new) work experience and suggest that occupational health professionals work more closely with experts in design thinking to link the respective knowledge domains. All the more because strategies and methods of occupational health psychologists are very compatible with design thinking: they are by principle highly participatory and iterative, and they utilize various forms of brainstorming, visualization, and planning techniques such as drawing team visions, building mental models and narratives, mapping of job demands and resources, creating visual objects for progress evaluation, or using Kanban boards, for example (Abildgaard et al, 2020;Ipsen et al, 2020;von Thiele Schwarz et al, 2016;von Thiele Schwarz et al, 2021). Such methods have also been digitalized, as in the example of the https://wecoach.ch, which was built as a DOHI for improving working conditions (Grimm et al, 2020).…”
Section: Co-creating a Human-centered Future Of Workmentioning
confidence: 99%